Ballistic Performance of Bulletproof Vests Reinforced with Hybrid Composites of Eichhornia Fiber and Kevlar Dupont Armortex - Fajar Paundra; Ahmad Tito; Abdul Muhyi; Devia Gahana Cindi Alfian; Farid Nanda Syanur; Fajar Perdana Nurulloh; Ariyo Nurachman Satiya Permata; Fattah Maulana; Akhmad Nurdin; Sri Hastuti (Universitas Sultan Ageng Tirtayasa, 2026)
The fiber stacking sequence in hybrid composites of Eichhornia and Kevlar Dupont Armortex significantly influences ballistic resistance. This study aimed to investigate the effect of different stacking sequences of Eichhornia/Kevlar hybrid composites on ballistic performance. The materials employed were woven Eichhornia fibers, Kevlar Dupont Armortex, and polyester resin. The composites were fabricated using the vacuum bagging method at 14 psi for 24 h, followed by curing at 80 °C for 60 min. Two stacking configurations were examined: Armortex Eichhornia Armortex (AEA) and Eichhornia Armortex Eichhornia (EAE). Ballistic testing was conducted in accordance with NIJ 0101-07, referring to ballistic threat level NIJ 0123.00 (NIJ HG1). The results revealed that the fabricated hybrid composites were unable to resist MU1-TJ 9 × 19 mm bullets fired from a Tanfoglio Stock III 919 pistol with a kinetic energy of 885 J, leaving impact marks with varying diameters depending on the stacking configuration. Further observations indicated that the hybrid composites experienced fiber displacement leading to crack formation, fibrillation of constituent fibers, and interlayer delamination.